Anisotropy, disorder and frustration in magnetic nanoparticle systems and spin glasses - Jönsson, Petra (Uppsala universitet, Institutionen för materialvetenskap, 2002)
Magnetic properties of nanoparticle systems and spin glasses have been investigated theoretically, and experimentally by squid magnetometry. Two model three-dimensional spin glasses have been studied: a long-range Ag(11 at% Mn) Heisenberg spin glass and a short-range Fe0.5Mn0.5TiO3 Ising spin glass. Experimental protocols revealing ageing, memory and rejuvenation phenomena are used. Quantitative analyses of the glassy dynamics within the droplet model give evidences of significantly different exponents describing the nonequilibrium dynamics of the two samples. In particular, non-accumulative ageing related to temperature-chaos is much stronger in Ag(11 at% Mn) than in Fe0.5Mn0.5TiO3. The physical properties of magnetic nanoparticles have been investigated with focus on the influence of dipolar interparticle interaction. For weakly coupled nanoparticles, thermodynamic perturbation theory is employed to derive analytical expressions for the linear equilibrium susceptibility, the zero-field specific heat and averages of the local dipolar fields. By introducing the averages of the dipolar fields in an expression for the relaxation rate of a single particle, a non trivial dependence of the superparamagnetic blocking on the damping coefficient is evidenced. This damping dependence is interpreted in terms of the nonaxially symmetric potential created by the transverse component of the dipolar field. Strongly interacting nanoparticle systems are investigated experimentally in terms of spin-glass behaviour. Disorder and frustration arise in samples consisting of frozen ferrofluids from the randomness in particle position and anisotropy axes orientation. A strongly interacting system is shown to exhibit critical dynamics characteristic of a spin-glass phase transition. Ageing, memory and rejuvenation phenomena similar to those of conventional spin glasses are observed, albeit with weak temperature-chaos effects.